Policy, Profits, and Palm Oil: A Bibliometric Synthesis of the Economic and Environmental Payoffs (West Science Interdisciplinary Studies, 2025)
The global palm oil industry sits at the nexus of economic growth and environmental sustainability, generating both substantial financial returns and significant ecological concerns. This study presents a bibliometric synthesis of scholarly literature on palm oil, with particular focus on the interplay between policy frameworks, profitability, and environmental outcomes. Using the Scopus database, a total of relevant publications from 2000 to 2024 were analyzed through VOSviewer software to identify trends in co-authorship, citation patterns, and keyword co-occurrence. The findings reveal that "palm oil" and "sustainable development" serve as thematic anchors linking diverse domains such as biofuel production, deforestation, land use change, and economic valuation. Temporal analysis indicates a thematic evolution from environmental critiques toward techno-economic innovation and governance mechanisms. Collaboration networks highlight Malaysia and Indonesia as dominant contributors, with growing international partnerships across Europe, North America, and Asia. Despite the increasing academic attention to sustainability, the study identifies gaps in policy evaluation and interdisciplinary integration. The discussion offers actionable insights and policy recommendations to bridge these gaps, emphasizing the need for holistic, evidence-based strategies that align economic development with environmental integrity in palm oil governance.